First comprehensive report on distribution of histologically confirmed oral and maxillofacial pathologies; a nine year retrospective study - Shabir, Hina; Muhammad Irshad; Durrani, Sofia Haider; Sarfaraz, Amna; Nazir Arbab, Kanwal; Khattak, Maria Tasneem (Journal of the Pakistan Medical Association, 2022)
Objective: To report the distribution of oral and maxillofacial pathologies diagnosed histologically in laboratory. Methods: The retrospective descriptive cross-sectional study was conducted at Rehman Medical Institute, Peshawar, Pakistan, and comprised biopsied lesions submitted to the institutional laboratory from 2010 to 2019. Data on gender, age, site of the lesion and histopathological diagnosis was retrieved from the records. Data was analysed using Microsoft Excel. Results: Of the 986 histologically confirmed cases, 545(55.27%) related to males and 441(44.72%) to females. The overall mean age of the patients was 43.20+19.85. Tongue was the most affected site 159(16.1%). The most common diagnostic category was malignant tumours 338(34%), followed by salivary gland pathology 162(16%), and cysts and odontogenic tumours 138(14%). The most common histopathological finding was oral squamous cell carcinoma 249(25.2%), and pleomorphic adenoma was the most common benign tumour 103(10.4%). Conclusion: Oral squamous cell carcinoma was the most common malignancy, while pleomorphic adenoma was the most common benign tumour. Key Words: Oral and maxillofacial lesions, Prevalence, Histopathology, Benign lesions, Malignant lesions.